Exploring the Experiences of People Vlogging about Their Mental Health During the COVID-19 Lockdown: A Thematic Analysis - Andriopoulou, Panoraia; Servina, Natalina Paola Samanta (Journal of Psychology and Psychotherapy Research, 2021)
Background: The mental health consequences of the COVID-19 lockdown are of great concern. The true extent of these difficulties is not yet known, as there is only a limited number of preliminary survey-based studies. Aims: The present study aimed to explore how individuals experienced mental health difficulties during the lockdown, as they vlogged about them on YouTube. Methods: YouTube was searched systematically using relevant keywords (“Lockdown”, “Mental health”, “Depression” and “Anxiety”) and a set of 42 vlog videos was identified as eligible for analysis. Videos were transcribed verbatim and analysed using thematic analysis. Results: Five overarching themes were identified: instability and extreme states; sense of loss; intolerance of ambiguity; barriers to improvement; and helpful practices. Conclusions: These themes demonstrated that individuals are essentially prone to the experience of mental health issues during the lockdown. The implications of the findings are discussed, particularly in relation to the need for pandemic-tailored psychosocial interventions.